Retention Strategy for Health Professionals: A Descriptive Study - Mirza Mohamod Zahir Uddin Bhuiyan (Medical Science: Trends and Innovations Vol. 12, 2025)
Background: Effective medical service and enough health professionals are required to develop quality health service. Recruitment, retention of the health workforce and increased health financing in developing countries are important to achieve the targets of Sustainable Development Goal 3 to ensure healthy lives and promote well-being for all at all ages. The aim of this study is to find out the perception and opinions from the resigned medical practitioners and professional nurses of Mankweng Academic Hospital regarding the retention of health professionals, and from which retention initiatives can be implemented from the data gathered. Methods: An observational retrospective descriptive quantitative design associated with all resigned medical practitioners and professional nurses who quited from Mankweng Academic Hospital from January 2018 to December 2022. Results: A total of 121 medical practitioners and professional nurses resigned from January 2018 to December 2022. Among them, 74 were medical practitioners and 47 professional nurses. Lack of prospects advancement (26%), relocation (26%), and promotion (19%) were the important associated factors responsible for quitting the job among the group of medical practitioners. Promotion (34%), poor working conditions (13%), and work-related stress (13%) were the main reasons for the resignation of the professional nurses. Over 22% of medical practitioners proposed to increase the number of staff, and 49% of the professional nurses advocated increasing the number of staff. Conclusion: Opinions of the resigned medical practitioners and professional nurses were to emphasize increasing the number of Health professionals. Adequate staffing is necessary in the health sector. Increasing the number of health professionals is imperative, and equally, enhanced promotions should be considered to retain the employee.